2019
DOI: 10.1111/epi.16060
|View full text |Cite
|
Sign up to set email alerts
|

Impaired vocal communication, sleep‐related discharges, and transient alteration of slow‐wave sleep in developing mice lacking the GluN2A subunit of N‐methyl‐d‐aspartate receptors

Abstract: Objective Glutamate‐gated N‐methyl‐d‐aspartate receptors (NMDARs) are instrumental to brain development and functioning. Defects in the GRIN2A gene, encoding the GluN2A subunit of NMDARs, cause slow‐wave sleep (SWS)‐related disorders of the epilepsy‐aphasia spectrum (EAS). The as‐yet poorly understood developmental sequence of early EAS‐related phenotypes, and the role of GluN2A‐containing NMDARs in the development of SWS and associated electroencephalographic (EEG) activity patterns, were investigated in Grin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 53 publications
(145 reference statements)
1
19
0
Order By: Relevance
“…In addition, perisylvian, prefrontal, and cingulate cortices undergo a long developmental process and are sensitive to environmental influences and intrinsic physiological perturbations, as ED, throughout childhood and adolescence (57,58). GRIN2A knocked out mice, a genetic model of epilepsyaphasia spectrum (encompassing CECTS, Landau-Kleffner syndrome, and ESES), displayed impaired vocal communication as well as microstructural diffuse brain alteration in a specific development time window, corresponding to the human schoolage/pre-adolescence (59,60). In CECTS, morphometric analyses revealed diffuse increases in gray matter volumes that inversely correlated with age (49).…”
Section: The Age-dependence Effect Of Ed Density On Normal Neurodevelmentioning
confidence: 99%
“…In addition, perisylvian, prefrontal, and cingulate cortices undergo a long developmental process and are sensitive to environmental influences and intrinsic physiological perturbations, as ED, throughout childhood and adolescence (57,58). GRIN2A knocked out mice, a genetic model of epilepsyaphasia spectrum (encompassing CECTS, Landau-Kleffner syndrome, and ESES), displayed impaired vocal communication as well as microstructural diffuse brain alteration in a specific development time window, corresponding to the human schoolage/pre-adolescence (59,60). In CECTS, morphometric analyses revealed diffuse increases in gray matter volumes that inversely correlated with age (49).…”
Section: The Age-dependence Effect Of Ed Density On Normal Neurodevelmentioning
confidence: 99%
“…In animal models, homozygotes of targeted null GRIN2A exhibited jumpiness, increased locomotor activity, and loss of analgesic tolerance after repeated morphine doses ( Sakimura et al, 1995 ; Kadotani et al, 1996 ). In Grin2a knockout mice, spontaneous epileptiform discharges were detected ( Salmi et al, 2018 , 2019 ). These clues indicated that loss of GluN2A protein was associated with increased neuronal excitability.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that androgen receptor (Ar) in the main circadian clock of suprachiasmatic nucleus regulates the effect of light on male activity [ 47 ]. In addition, changes in GluN2A, a N-methyl-d-aspartate receptor (NMDAR) subunit encoded by GRIN2A, are associated with neurodevelopmental disorders and are critical to sleep-related physiological and pathological processes [ 48 , 49 ]. The aforementioned analysis showed that berberine can achieve therapeutic effect by influencing the expression of key disorder factors.…”
Section: Discussionmentioning
confidence: 99%